Discrete element modelling of the in-plane and out-of-plane behaviour of dry-joint masonry wall constructions. (1st April 2017) - Bui, T.T.; Limam, A.; Sarhosis, V.; Hjiaj, M.
Highlights: An experimental collection is provided to develop a reliable model. Modeling of in-plane/out-of-plane behaviour of dry-joint masonry by DEM. Model developed is capable to represent crack/load capacity of dry-joint masonry. Abstract: This paper aims to improve knowledge on the suitability of the discrete element method (DEM) to simulate the in-plane and out-of-plane behaviour of different in-configuration structural masonry walls constructed with dry joints. The study compares the results obtained from laboratory tests against those predicted using the three-dimensional distinct element 3DEC software. Significant features of the structural behaviour shown by the walls are discussed and conclusions on their ultimate capacity and failure mechanisms are addressed. A key feature of the DEM is the important role that brick discontinuities, i.e. joints, play in the mechanics of masonry. Within DEM, the bricks were modelled as continuum rigid elements while the joints were modelled by line interface elements represented by the Mohr-Coulomb law. The analysis of the results showed that the model developed is capable of representing the crack development and load carrying capacity of masonry structures constructed with dry joints with sufficient accuracy. Moreover, a collection of experimentally verified material parameters is provided to be used by other researchers and engineers and to develop a reliable model to solve engineering challenges worldwide.